Percepción del dolor y niveles de ansiedad durante la aplicación de anestesia local odontológica con vasoconstrictor en pacientes adultos sanos - Segura García, Diego Alejandro (2017)
Anxiety is an emotional reaction that leads to stress, apprehension, nervousness, caused by past negative experiences. On the other hand, pain is an unpleasant sensory experience caused by external stimuli. Objective: To determine the self-perception of pain and anxiety levels during the application of local dental anesthesia with vasoconstrictor in healthy adult patients. Materials and methods: This study was carried out from a sample of 30 healthy adult patients who attended the dental clinic of the UDLA in the period of April-May 2017, with ages ranging from 20 to 60 years. The information will be collected in the comprehensive clinic of the University of the Americas by the researcher. To measure the self-perception of patients' pain during the application of the anesthetic, the Visual Analogue Scale (VAS) will be used. This information will be taken in two moments: needle puncture and anesthetic administration respectively, while the Modified Dental Anxiety Scale (MDAS) will be used to determine the levels of anxiety experienced by patients prior to the application of the anesthetic. Results: Patients with higher anxiety reported higher levels on the pain scale, especially at the time of administration of the anesthetic. Conclusion: It has been concluded that there is a relationship between self-perception of pain and anxiety levels, since some patients who reported greater anxiety had higher levels on the pain scale